ASSESSING THE PERFORMANCE OF RACINUS COMMUNIS (L.) IN DECONTAMINATING HEAVY METALS POLLUTED SOIL USING PHYTOEXTRACTION STRATEGY - Abubakar Salisu; Ibrahim Mohammed Ibrahim (Engineering Heritage Journal)
Globally, our environments (soil, water and air) are increasingly exposed to heavy metals (HMs) contaminations through natural and anthropogenic activities. Thus, it is a matter of great significance to remediate these metals from the ecosystem in order to maintain a safe and healthy environment. The research was carried out to evaluate the phytoextraction capacity of Racinus communis (L) grown on contaminated soils with HMs obtained from three sites in urban Kano. The physicochemical parameters of the soil samples were analysed using Near-Infrared spectrometer (NIRS D-2500) and other standard procedures. The HMs concentrations were analyzed using Micro Plasma Atomic Emission Spectrometer (MPA-ES, Model 4210). The degree of HMs contaminants were evaluated using Mueller’s Geoaccumulation Index (Igeo). Data were statistically analysed using one way Analysis of Variance at P<0.05. The physicochemical results revealed that all the soil samples were sandy-loam in texture and slightly acidic with pH values ranging between (6.11±0.02-5.02±0.06). Other concentration of soil physicochemical parameters varies across the soil samples. The results of the HMs analyses across the soils revealed highest concentrations of Fe (311.02 ±0.04 mg/kg), Cu (208.62±0.01 mg/kg) and Zn (112.04±0.04 mg/kg) in soil sample A, Pb (34.03±0.16 mg/kg) and Cr (4.63±0.03mg/kg) were observed to be higher in soil sample C, while the highest concentration of Cd (1.20±0.00 mg/kg) was recorded in soil sample B. Relatively all the concentrations of HMs in the contaminated soil samples after the experiment were defined uncontaminated to moderately contaminated based on Igeo values. The findings provide scientific evidence that R. communis can be used as a veritable tool for the control of HMs pollution in the soil.